From the Bamiyan Grottoes to the Yungang Grottoes in China:An Exploration of historical traces and reasons of cultural blending - Zhou, Kanhe (Transactions on Social Science, Education and Humanities Research, 2024)
The Bamiyan Grottoes in Afghanistan are the epitome of cultural integration , integrating Greek , Persian , Indian , White Huns and other cultures . The Yungang Grottoes in China , which were influenced by the Bamiyan Grottoes , not only have many characteristics of the combination of Chinese and foreign cultures , There is also the imprint of the cultural integration of the Chinese nation . There are three reasons for cultural integration : first , the grottoes have a superior geographical location ; second, the superior geographical location makes the area where the grottoes are located not only a transportation hub , but also a place full of political and cultural disputes and friction, thus cultural exchanges are extremely frequent ; Third , local rulers implemented proper cultural decisions and treated different cultures with an inclusive attitude .